EFEKTIVITAS PENERAPAN MEDIA PEMBELAJARAN POWTOON TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN IPS - Scolastika, Gracia Efra; Barella, Yusawinur; Aminuyati, Aminuyati; Okianna, Okianna; Atmaja, Thomy Sastra (Universitas Tanjungpura, 2022)
This study aimed to determine the effectiveness of the Powtoon application on the learning outcomes of class VIII social studies. This study used a quantitative approach in the form of a quasi-experimental study. The sample of this study comprises 8th-grade B and 8th-grade C students, up to 22 students per class. The data collection techniques used were assessment techniques and documentary study, as well as data collection tools in the form of post-tests and research documents. The results showed that the mean scores from the post-test for the experimental group was 73.81, and the control class was 59.54, with a difference of 14.27. As a result, there are significant differences in learning outcomes. In the normality test, the significance value of the experimental group was 1680.05, while the significance value of the control group was 1430.05. Therefore, the data is in a normal distribution. In the hypothesis test, the sig. value (2-tailed) is 0.0000.05, with an effect size of 1.070.08, which is in the high category. The results showed that the Powtoon application is effective and efficient for eighth-grade social studies learning outcomes.